CAD e engenharia reversa como ferramentas de auxílio na fabricação de cartuchos para próteses ortopédicas - Pereira, Edson Jorge Alcântara (2014)
The manufacturing of above and below-knee prosthesis starts by taking surfac measurements of the patient s residual limb. This demands the making of a cartridg with appropriate fitting and customized to the profile of each patient. The traditiona process in public hospitals in Brazil begins with the completion of a record file (according to law nº388, of July 28, 1999 by the ministry of the health) for obtaining o the prosthesis, where it is identified the amputation level, equipment type, fitting type material, measures etc. Nowadays, that work is covered by the Brazilian Nationa Health Service (SUS) and is accomplished in a manual way being used commo measuring tapes characterizing a quite rudimentary, handmade work and without an accuracy.In this dissertation it is presented the development of a computer integrate tool that it include CAD theory, for visualization of both above and below-knee prosthesis in 3D (i.e. OrtoCAD), as well as, the design and the construction a low cos electro-mechanic 3D scanner (EMS). This apparatus is capable to automatically obtain geometric information of the stump or of the healthy leg while ensuring smalle uncertainty degree for all measurements. The methodology is based on reverse engineering concepts so that the EMS output is fed into the above mentioned academi CAD software in charge of the 3D computer graphics reconstruction of the residualimb s negative plaster cast or even the healthy leg s mirror image. The obtained results demonstrate that the proposed model is valid, because it allows the structura analysis to be performed based on the requested loads, boundary conditions, material chosen and wall thickness. Furthermore it allows the manufacturing of a prosthesis cartridge meeting high accuracy engineering patterns with consequent improvement in the quality of the overall production process